Development and manufacturing of an Albatross-inspired tilt-wing drone - Escamilla, L.; Throneberry, G.; Sanchez, G.; Vasconcellos, R. [UNESP]; Abdelkefi, A.; AIAA (Amer Inst Aeronautics & Astronautics, 2020)
The need for improving drone systems becomes imperative. In order to enhance these systems, engineers are drawing from biological systems for inspiration to improve the overall endurance and flight characteristics of drones. One such organism, the Albatross, is studied and chosen to be the inspiration for a unique tilt-wing drone system. The aerodynamic characteristics of the Albatross wing are simulated and discussed. Additionally, a tilting actuation mechanism is researched, and different setups are considered. Several wings are created by hot-wiring foam into the desired airfoil shapes. Moreover, the fuselage is designed on Fusion 360. Important design choices are highlighted and discussed.